Maned wolves retain moderate levels of genetic diversity and gene flow despite drastic habitat fragmentation - Mannise, Natalia; Cosse, Mariana; Gonzalez, Susana; Emmons, Louise H.; Barbanti Duarte, Jose Mauricio [UNESP]; Beccaceci, Marcelo D.; Maldonado, Jesus E. (Inter-research, 2017)
The maned wolf Chrysocyon brachyurus is the largest South American canid and categorized as Near Threatened on the IUCN Red List. The major threat to conservation efforts is the drastic reduction of suitable habitat for the species. A large portion of its range has been converted into farm and ranch lands as well as urban areas. To better understand the impact that these anthropogenic activities are having over the remaining populations across their current distribution range, we evaluated patterns of genetic variability and differentiation between them. We also compared these results with those obtained from captive maned wolves in order to make proper ex situ recommendations. We cross-amplified 12 microsatellite loci in maned wolf samples collected throughout their range (from Argentina, Brazil, Uruguay and Bolivia) and from captive stocks (from captive breeding centers and zoos in Brazil, Argentina and the USA). We found that wild populations retain moderate levels of genetic variability compared with other microsatellite studies on wild canids, and our structure analysis revealed 2 genetic clusters in wild samples, one of which included samples exclusively from Bolivia. This cluster could represent a different management unit with conservation priority. The captive stock population showed higher levels of genetic variability, with the ones from Brazil being the most genetically diverse stock. The USA stock showed strong genetic differences with all other groups. This is the first study to examine the patterns of genetic diversity of both wild and captive populations of maned wolves. These results should be incorporated into further population viability assessments and in the Maned Wolf Species Survival Plan.
Keywords: Canids; Population genetics; Microsatellite loci; Noninvasive genetic analysis